Application of Naphthalene-captopril Column for Pre-concentration and Determination of Trace Amount of Copper(II) in Waste Water Samples by Flame Atomic Absorption Spectrometry - ZAVVAR MOUSAVI, H. (Asian Journal of Chemistry, 2010)
A sensitive and selective pre-concentration method for the determination of copper(II) by flame atomic absorption spectrometry has been developed. Copper forms a complex with captopril. This complex is retained by naphthalenecaptopril adsorbent in a column with a height of ca. 2.5 cm. The adsorbed metal complex is then eluted from the column with nitric acid and its copper content is determined by flame atomic absorption spectrometry. The effect of different variables such as pH, reagent concentration, flow rate and interfering ions on the recovery of the analyte was investigated. The calibration graph was linear in the range 75-350 μg L-1 of copper in the initial solution. Detection limits (3σ, n = 10) of 23 μg L-1 and relative standard deviation 2.4 and 1.6 % at 200 and 300 μg L-1 level were obtained. This procedure was successfully applied to the determination of copper in waste water samples. Analytical recoveries of copper added to samples were 98-103 %.